Entrepreneurial Skills and Business Success in the Informal Sector: A Qualitative Study (Journal of Business Management and Accounting, 2015)
The informal sector’s activities account for a significant proportion in production, consumption, employment, and development. There are contrary arguments saying that the informal sector would shrink and disappear on its own when the level of economy advances in the country, but the trend nowadays shows the opposite, where there is an expansion, mainly in business operating in the urban areas. In early entrepreneurship research, it only focused on finding general individuality and motives of successful entrepreneurs, where entrepreneurs require capability like traits, knowledge, and specific skills in order to be capable of achieving success as an entrepreneur. Yet, research on the relationship between entrepreneurial skills and business success is scarce, especially in the informal sector because of availability of data in terms of management, worker training, growth potential, and access to the world market. In this case, this study focused on entrepreneurial skill which is the most important factor that contributes to business success in the informal sector. The result of this study showed that communication and negotiation skills are the most influencing skills for the success of business in the informal sector in Malaysia.